A LIGHTWEIGHT UAV-BASED LASER SCANNING SYSTEM FOR FOREST APPLICATION - Torres, Fernanda Magri; Tommaselli, Antonio Maria Garcia (Universidade Federal do Paraná, 2018)
Abstract Lightweight Unmanned Aerial Vehicles (UAVs) have become a cost effective alternative for studies which use aerial Remote Sensing with high temporal frequency requirements for small areas. Laser scanner devices are widely used for rapid tridimensional data acquisition, mainly as a complementary data source to photogrammetric surveying. Recent studies using laser scanner systems onboard UAVs for forestry inventory and mapping applications have presented encouraging results. This work describes the development and accuracy assessment of a low cost mapping platform composed by an Ibeo Lux scanner, a GNSS (Global Navigation Satellite System) antenna, an Inertial Navigation System Novatel Span-IGM-S1, integrating a GNSS receiver and an IMU (Inertial Measurement Unit), a Raspberry PI portable computer and an octopter UAV. The system was assessed in aerial mode using an UAV octopter developed by SensorMap Company. The resulting point density in a plot with trees concentration was also evaluated. The point density of this device is lower than conventional Airborne Laser Systems but the results showed that altimetric accuracy with this system is around 30 cm, which is acceptable for forest applications. The main advantages of this system are their low weight and low cost, which make it attractive for several applications.

Resumo Veículos aéreos não tripulados (VANT) leves tornaram-se uma alternativa de baixo custo para estudos que dependem de Sensoriamento Remoto aéreo com alta frequência temporal em pequenas áreas. Dispositivos de varredura a LASER são amplamente utilizados para aquisição rápida de dados tridimensionais, principalmente como uma fonte de dados complementar ao levantamento fotogramétrico. Estudos recentes utilizando sistemas de varredura a LASER embarcados em VANT para aplicações de inventário florestal e mapeamento apresentaram resultados positivos. Este trabalho descreve o desenvolvimento e avaliação de uma plataforma de mapeamento de baixo custo composto por um scanner Ibeo LUX, uma antena GNSS, um Sistema de Navegação Inercial Novatel SPAN-IGM-S1, que integra um receptor GNSS e uma Unidade de Medida Inercial, um computador portátil Raspberry Pi e um octóptero. O sistema foi avaliado para o modo aéreo usando um octocóptero desenvolvido pela empresa Sensormap. A densidade de pontos resultante em área com concentração de árvores também foi avaliada. A densidade de pontos obtida com este sistema é menor que a coletada por um sistema de varredura aérea LASER convencional, mas os resultados mostram que a precisão altimétrica com este sistema é de cerca de 30 cm, que é aceitável para aplicações florestais. As maiores vantagens deste sistema são o baixo peso e baixo custo que o torna atraente para várias aplicações.
Um sistema de varredura a laser leve baseado em VANT para aplicação florestal
Keywords: Mobile LASER Scanning System; UAV; mapping tool; point cloud; Sistema de Varredura a LASER móvel; VANT; ferramenta de mapeamento; nuvem de pontos